Study of Philosophy of Social Work as a profession in India - Rani, Rakhi (Innovative Research Thoughts, 2017)
Individuals with psycho-social difficulties and inadequacies in their connection with their social environment are the primary focus of social work, which is a profession that is focused with the treatment of these problems and deficiencies. This phenomena has continuously was in culture in some form or another, but it was only in the later decades of the nineteenth century that it had a scientific foundation. In the past, individuals, families, communities, and religious groups have helped those in need because they thought that "charity was a way to get to heaven, and because they thought that “humanism, philanthropy, humanitarian feeling, democratic ideology, equality of all citizens,” respect for other's rights, and respect for human dignity were important.